Safe handling of nanomaterials and other advanced materials at workplaces (Dortmund, 2015)
"A rising number of companies, especially small and medium enterprises (SME), are active in the field of nanotechnology. For safe development of this industry, forethought of occupational safety and health considerations is important. This guideline on good working practice with nanomaterials addresses research institutions as well as SME industries. Four decision criteria are presented that support the reader in deriving the appropriate occupational safety measures in a comprehensible way. These occupational safety measures are tailored to the defined groups of nanomaterials and follow the precautionary approach. They comply with the priority list of the STOP principle: substitution, technical measures, organisational measures and personal protection measures."